2002
DOI: 10.2337/diabetes.51.4.994
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Protects Pancreatic β-Cells From Apoptosis and Improves Islet Function/Survival After Transplantation

Abstract: Pancreatic islets transplanted to treat autoimmune type 1 diabetes often fail to function (primary nonfunction), likely because of islet ␤-cell apoptosis. We show that carbon monoxide (CO), a product of heme oxygenase activity, protects ␤-cells from apoptosis. Protection is mediated through guanylate cyclase activation, generation of cyclic GMP (cGMP), and activation of cGMPdependent protein kinases. This antiapoptotic effect is still observed when ␤-cells are exposed to CO for 1 h before the apoptotic stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
73
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 43 publications
7
73
0
1
Order By: Relevance
“…CO, a product of the HO-1-catalyzed enzymatic reaction, is thought to be the major mediator of these actions and can in return increase LPS-induced expression of IL-10 in macrophages (39). It has also recently been shown that HO-1 and CO protected pancreatic ␤-cells from apoptosis and improved islet function/survival after transplantation (22,40). A direct relationship between IL-10 and SOD has not been reported, but a number of studies have implicated the involvement of SOD in IL-10 -mediated protection.…”
Section: Discussionmentioning
confidence: 99%
“…CO, a product of the HO-1-catalyzed enzymatic reaction, is thought to be the major mediator of these actions and can in return increase LPS-induced expression of IL-10 in macrophages (39). It has also recently been shown that HO-1 and CO protected pancreatic ␤-cells from apoptosis and improved islet function/survival after transplantation (22,40). A direct relationship between IL-10 and SOD has not been reported, but a number of studies have implicated the involvement of SOD in IL-10 -mediated protection.…”
Section: Discussionmentioning
confidence: 99%
“…According to other studies about the tissue protective role of CO, the most efficacious concentration of CO ranges from Ϸ250 ppm to 1000 ppm. [12][13][14]16,17 The most beneficial concentration of CO may be specific for each species and each tissue. We cannot extrapolate the most efficacious condition of CO administration for the treatment of myocardial infarction in human beings from our data alone.…”
Section: Discussionmentioning
confidence: 99%
“…HOderived CO reduces vasoconstriction, thus lowering blood pressure and increasing tissue blood flow. 10,11 Exogenous CO was reported to reduce ischemia-reperfusion injury of lung and apoptosis of pancreatic ␤ cells via activating soluble guanylate cyclase, 12,13 and to reduce hepatic ischemia-reperfusion injury, apoptosis of endothelial cells, and inflammation through p38 mitogen-activated protein kinase (p38MAPK) pathway. 14 -16 Motterlini et al reported that CO-releasing molecules could reduce the cardiac muscle damage induced by ischemia-reperfusion via activation of mitochondrial K ATP channel in an ex vivo model; 17 however, the precise mechanism of tissue protection by CO is still controversial.…”
mentioning
confidence: 99%
“…Assays were performed using a modified crystal violet method (23,24). Briefly, ␤-insulinoma (␤-TC 3 ) cells were pretreated (30 min) with 0.01 mol/l actinomycin D (Calbiochem, Kilsyth, Australia) before the addition of 100, 500, or 1000 units/ml of recombinant mouse tumor necrosis factor (TNF)-␣ (R&D Systems, Minneapolis, MN).…”
mentioning
confidence: 99%